2021
DOI: 10.4269/ajtmh.20-1257
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Encephalitis Caused by Balamuthia mandrillaris in a 3-Year-Old Iranian Girl

Abstract: It is about half a century since free-living amoebae were recognized as pathogenic organisms, but there is still much we should learn about these rare fatal human infectious agents. A recently introduced causative agent of granulomatous amoebic encephalitis, Balamuthia mandrillaris, has been reported in a limited number of countries around the world. A 3-year-old girl was referred to our tertiary hospital because of inability to establish a proper diagnosis. She had been experiencing neurologic complaints incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Balamuthia mandrillaris and Naegleria fowleri are two highly fatal, protozoan pathogens distributed widely in the environment [3,[26][27][28]. Furthermore, although these parasites are distributed globally, they favor warmer temperatures; hence, global warming is of concern [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Balamuthia mandrillaris and Naegleria fowleri are two highly fatal, protozoan pathogens distributed widely in the environment [3,[26][27][28]. Furthermore, although these parasites are distributed globally, they favor warmer temperatures; hence, global warming is of concern [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study on the soil gene search of B. mandrillaris demonstrated that this type of opportunistic ameba can spread to wider climatic areas, even in areas characterized by blizzards [11]. Consequently, during the last few years, several Asian regions, such as South Korea [12,13], Japan [11,14], Thailand [15][16][17], India [18], Iran [19], and China [20][21][22][23], have reported 64 cases of infection with B. mandrillaris, of which 32 were recently reported in 12 provinces in China. Patients infected Diagnosing Balamuthia mandrillaris amebic meningoencephalitis in a 64-year-old woman from the Southwest of China by B. mandrillaris can present symptoms of subacute to chronic cutaneous lesions or central nervous system (CNS) infection with granulomatous amebic encephalitis.…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, there is only one case report of Primary Amoebic Meningoencephalitis, seen in an infant, and also a case of Balamuthia mandrillaris Encephalitis in a 3‐year‐old girl. Other brain diseases related to FLA is not reported yet mainly due to unawareness of physicians and laboratory technicians 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…Other brain diseases related to FLA is not reported yet mainly due to unawareness of physicians and laboratory technicians. 14,15 Several studies demonstrated DA, cerebral abscess, and cutaneous acanthamoeba infection in organ-transplant recipients such as patients with liver, hematopoietic stem cell, lung, and kidney transplant patients. [16][17][18][19] In 2007, the first reported case of DA was published by Barete et al in a 39-year-old heart transplant patient who was infected with Acanthamoeba T5 genotype.…”
Section: Introductionmentioning
confidence: 99%